In vitro Antiviral Activity of Cat’s Claw (Uncaria tomentosa) bark Extract Against Human Influenza A Virus - Makau, Juliann N; Talaam, Keith K; Odiwuor, Mike; Majanja, Janet M; Musenjeri, Sophia; Rahmasari, Ratika; Khamadi, Samoel A; Watanabe, Ken (Pharmaceutical Sciences and Research, 2025)
Influenza A viruses mutate very fast and this leads to the development of resistance to antivirals, hence the need to find new therapeutics. Due to their extensive traditional use, natural products are crucial resources for the discovery of drugs. Cat’s claw (Uncaria tomentosa), is a tropical vine known for various health benefits and in this study we evaluated its anti-influenza activity. Pulverized material of the stem bark was extracted using 80% ethanol, hot water, and 1% sodium bicarbonate. The extracts were dried and dissolved in dimethylsulfoxide before testing for cytotoxicity and antiviral activity using crystal violet assay. The extracts exhibited antiviral activity with a 50% inhibitory concentration range of 2.3 - 6.2 µg/mL. The 1% sodium bicarbonate extract had the least 50% cytotoxic concentration of 125 µg/mL and was used for further analyses. It was effective against several human influenza A virus strains including an oseltamivir-resistant clinical isolate of the 2009 H1N1 pandemic influenza. Time-of-addition experiments showed significant suppression of virus replication when the virus was pretreated with the extract before infecting to cells and also when the virus and extract were co-administered to the cells; suggesting that the extract was inactivating the virus. Oseltamivir was used as a positive control and only suppressed late stages of virus replication. These results were consistent with the hemagglutination inhibition assay data which showed direct virucidal activity on influenza virus particles. Our data demonstrates possible future use of Cat’s claw in influenza management. However, more investigation is needed to identify the bioactive components.